UAVs as a tool for optimizing boat-supported flood evacuation operations - Moussa, Lara G.; Diaconu, Raluca; Watt, Michael S.; Muñoz, Enrique; Casado, Monica Rivas; Broadbent, Eben North; Bruscolini, Margherita; Doaemo, Willie; Mohan, Midhun (MDPI, 2024)
The frequency and intensity of flood events are increasing year by year as a result of climate change. This poses significant threats to human settlements and adversely affects biodiversity, agriculture, and infrastructure. One of the most prominent and traditional flood evacuation approaches is through the use of boats. Nonetheless, serious challenges exist with respect to determining the optimal deployment locations, routes, and timing. Given research advances in the Unmanned Aerial Vehicles (UAVs) sector—and their ability to offer real-time data and aerial monitoring services—we argue that their applications could help enhance boat-supported flood evacuation operations. In this opinion piece, we explore new opportunities for disaster management and underscore the advantages of integrating UAVs into flood evacuation methodologies, including areas of rapid field assessment, optimal route planning, and improved coordination between rescue boats. Notwithstanding the potential of UAVs, we emphasize several gaps to be explored in terms of large-scale data management/processing, regulatory limitations, and technological know-how. Furthermore, we provide recommendations for bolstering boat deployment protocols, disaster preparedness training programs, policy frameworks, and emergency response systems, which could maximize their efficacy in flood evacuation scenarios.
Keywords: 46 Information and Computing Sciences; 40 Engineering; flood rescue services; disaster management; climate change; Unmanned Aerial Vehicles; drones; remote sensing